Contemporary techniques in percutaneous coronary intervention for bifurcation lesions. (3rd October 2018) - Collet, Carlos; Mizukami, Takuya; Grundeken, Maik J.
ABSTRACT: Introduction : Treatment of coronary bifurcation lesions with contemporary state-of-the-art percutaneous coronary intervention (PCI) is still associated with higher rate of adverse cardiovascular events compared to non-bifurcation lesions. Bench testing and virtual computer modeling have increased our understanding of bifurcation PCI guiding refinement in bifurcation techniques. New insights on bifurcation PCI have the potential to further improve clinical outcomes in patients presenting with bifurcation lesions. Areas covered : The present manuscript aims to review the methods for bifurcation lesion assessment and treatment strategy step by step supported on bench and clinical evidence. Expert commentary : Invasive pressure-wire evaluation is essential to determine the appropriateness of bifurcation PCI, particularly in intermediate coronary stenosis. Treatment strategy relies on four parameters: diameters of the three segments of the bifurcation; lesion length and plaque distribution; and bifurcation angle. The optimal technique for bifurcation PCI is still debated, an individualized approach with an initial provisional side branch stenting strategy seems to be suitable in the 75 to 95% of patients. For more complex bifurcations, two-stent techniques may be required with increasing evidence supporting the usefulness of the double kissing balloon crush (DK-crush) technique.